1, 3, 4-Oxadiazole-naphthalene hybrids as potential VEGFR-2 inhibitors: design, synthesis, antiproliferative activity, apoptotic effect, and in silico studies. (1st January 2022) - Hagras, Mohamed; Saleh, Marwa A.; Ezz Eldin, Rogy R.; Abuelkhir, Abdelrahman A.; Khidr, Emad Gamil; El-Husseiny, Ahmed A.; El-Mahdy, Hesham A.; Elkaeed, Eslam B.; Eissa, Ibrahim H.
Abstract: In the current work, some 1, 3, 4-oxadiazole-naphthalene hybrids were designed and synthesised as VEGFR-2 inhibitors. The synthesised compounds were evaluated in vitro for their antiproliferative activity against two human cancer cell lines namely, HepG-2 and MCF-7. Compounds that exhibited promising cytotoxicity (5, 8, 15, 16, 17, and 18 ) were further evaluated for their VEGFR-2 inhibitory activities. Compound 5 showed good antiproliferative activity against both cell lines and inhibitory effect on VEGFR-2. Besides, it induced apoptosis by 22.86% compared to 0.51% in the control (HepG2) cells. This apoptotic effect was supported by a 5.61-fold increase in the level of caspase-3 compared to the control cells. Moreover, it arrested the HepG2 cell growth mostly at the Pre-G1 phase. Several in silico studies were performed including docking, ADMET, and toxicity studies to predict binding mode against VEGFR-2 and to anticipate pharmacokinetic, drug-likeness, and toxicity of the synthesised compounds.